PENGARUH TINGKAT KESEHATAN KEUANGAN DAN PRUDENT AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN SEBELUM DAN SESUDAH IMPLEMENTASI IFRS PADA PERUSAHAAN PEMBIAYAAN DI BURSA EFEK INDONESIA - Hermanto, Hermanto; Adibuwono, Sigit (Jurnal Ekonomi : Journal of Economic, 2017)
IFRS Implementation is an important issue in preparing a financial statement. The purpose of this research is to examine the effectual difference of  health financial ratio toward finacial statement quality and use of Prudent Accounting as a moderating variable before and after implementation of IFRS. The sample used are financial companies that were registered in the Indonesian stock exchange (BEI) between 2008-2016, through secondary data resource and sample data collection  through the purposive sampling method. The hypothesis was tested through Moderating Regression Analysis (MRA). The result of this research reveals that Capital Ratio, Net Perfoming Loan (NPF) dan Gearing Ratio have different effects toward a financial statement’s quality and Prudent accounting has influence over the relationship between Gearing ratio toward a financial statement before and after implementation of IFRS. The reasearch reveals that the prudent variable is the most influental variable prior to IFRS implementation and a variable moderating prudent toward Gearing ratio is most influental variable after IFRS implementation.  Keywords : capital ratio, non performing finance ratio, return on asset